The Instructional Human Resource Planning In Improving Quality Learning In Educational Institutions - Yudiarso, Agus Wahju; Fuadi, Imam; Sujianto, Agus Eko; Rohmah, Liatul (Journal of Instructional and Development Researches, 2025)
Islamic educational institutions are currently competing to get students and get quality human resources to improve the quality of the institution. Human resources are an important element because they play an active role in improving the quality of the institution. Human resources are the driving force of educational institutions that determine the quality of the institution. The purpose of this study is to formulate how human resource management is carried out at the Amanatul Ummah International Standard Madrasah Education Institution with a research focus on planning, recruitment, placement and, and development of human resources in improving the quality of institutions at MBI Amanatul Ummah Pacet Mojokerto the phenomenon in its entirety. Data collection techniques using in-depth interviews, field observations and documentation as supporting. The results of the study found that human resource planning refers to the needs of students as customers, while recruitment refers to the need to maintain quality. Placement and development of human resources at the Amanatul Ummah International Standard Madrasah are based on the results of the evaluation of the teacher council, advice from the kyai of the pesantren. The results of the study also showed that the right recruitment of human resources can improve the quality of the institution. Human resource development has an effect on better student services. This study concludes that improving the quality of institutions can be done through recruitment, evaluation, advice and development or read as a theory in improving the quality of institutions